Are We Still Dependent? Academic Dependency Theory After 20 Years. Issue 1 (23rd February 2022) - Tenzin, Jinba; Lee, Chengpang
Abstract: Academic dependency theory has attracted increasing attention in academia in the last two decades, especially during the last decade. Syed Farid Alatas, a Singapore‐Malaysia based sociologist, has contributed significantly to the popularization of the idea of academic dependency through theorizing and foregrounding the conditions of dependency in Western‐dominated knowledge production and the global division of academic labor. The growing importance of this idea as applied in Asian contexts is however inseparable from the reconfiguration of the world‐systems in which Asia and especially China have achieved great advancement economically and otherwise. In line with this transformation, we have seen an enhanced effort in Asia and the Global South towards decolonization and indigenization in educational and academic domains. We have therefore organized this special issue to engage critically with Alatas's theory and to rethink the status quo of dependency, decolonization and indigenization in Asia, particularly East Asia, in response to a new development in global and local higher education and research. To close our discussion, we call for an action‐based initiative to address and transform the circumstances of dependency and for more genuine global collaborations.